Innate Nectar Plant Attraction Is Primarily Visually‐Guided but Olfactory‐Stimulated in North American Monarch Butterflies - Darene A. E. Assadia; Delbert A. Green II (Ecology and Evolution)
ABSTRACT In flower‐visiting insects, innate sensory preferences facilitate efficient foraging strategies in complex natural environments. Here we describe a nonforced choice assay to investigate innate attraction to a common nectar resource (Lantana camara) in naïve monarch butterflies (Danaus plexippus). We find that monarch butterflies have an innate attraction to L. camara in our assay. Visual cues are necessary and sufficient for sustained attraction at the tested range. However, olfactory cues increase the salience of visual cues for sustained attraction. The identities of the specific attractive visual or olfactory cues are not resolved. Altogether, this simple nonforced choice assay is suited to reveal quantitative differences in innate attraction in monarchs and, presumably, other insects.